Efficiency Analysis of Indonesian Sharia Banks - Nur Khalimah; Edy Yusuf Agung Gunanto (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
The development of Islamic banking in Indonesia is still not optimal, so it requires performance improvement. It is necessary to measure efficiency and productivity to achieve predetermined targets. This study measures the level of efficiency of 12 Islamic commercial banks in Indonesia for the 2016-2018 period using DEA (Data Envelopment Analysis), method with the assumption of CRS (Constant Return to Scale) and maximizing output. Furthermore, the malmquist index analysis is to see the productivity level of Islamic commercial banks. The results show that the overall efficiency of Islamic commercial banks in Indonesia has decreased. In 2016, the average efficiency of Islamic commercial banks was 100 percent. In 2017 the average efficiency was 99.93 percent with 3 Islamic commercial banks that were not efficient. In 2018 the average efficiency was 98.4 percent with 2 Islamic commercial banks that were not efficient. The results of the malmquist index analysis in 2017, there were 8 Islamic commercial banks increasing returns to scale, while 4 Islamic commercial banks decreasing returns to scale. In 2018, 11 Islamic commercial banks increasing returns to scale and 1 Islamic commercial banks decreasing returns to scale.Keywords: Efficiency, productivity, DEA, Islamic Bank.